The interface of atherosclerosis and thrombosis: basic mechanisms - Peter Libby (1998)
Occlusive vascular disease most often results from thrombosis superimposed on atherosclerotic plaque. Disruption of plaque exposes thrombogenic substances within the plaque to blood and may result in thrombotic occlusion of the affected vessel. Mural thrombi may be incorporated into plaque, enhancing the evolution of atherosclerotic lesions. inflammation plays a key role in the formation and complication of atherosclerosis. inflammatory mediators regulate processes that determine the composition of the plaque's fibrous cap, a structure that separates blood from the thrombogenic lipid core. Several inflammatory mediators control the release of metalloproteinases (enzymes that break down cap constituents) from smooth muscle cells, macrophages and other cells within plaque. inflammatory mediators also control the production of connective tissue matrix by cells in the plaque. Factors involved in coagulation, such as thrombin, can regulate non-thrombotic functions of vascular wall cells such as smooth muscle proliferation or cytokine release. The many mechanisms involved in arterial occlusive disease present numerous points at which intervention with pharmacologic agents may prove effective in lowering the risk of acute arterial thrombotic complications.